Investigation of Total Antioxidant Status and Total Oxidant Status with Seizure Types in Patients with Epilepsy - TAŞLIDERE, BAHADIR; TAŞLIDERE B.; USLU, FERDA; USLU F.; SÖNMEZ, ERTAN; SÖNMEZ E.; SELEK, ŞAHABETTİN; SELEK Ş. (My University, 2022)
BACKGROUND/AIMS: As epilepsy is a complex disease group, it is difficult to diagnose and classify. Oxidative stress plays a vital role in the pathogenesis of epilepsy. This study investigated the total oxidant/antioxidant status levels in patients with focal onset and generalized onset seizures. The results we obtained may help find the etiological cause in patients with seizure complaints and may guide their treatment. In addition, knowing the seizure type of the patient can give an idea about the prognosis of their disease.MATERIALS AND METHODS: The total number of patients included in this prospective study was 58. There were also 57 people in a control group. The patients were classified according to their type of seizure: focal or generalized onset. The serum oxidative stress index (OSI) and total oxidant/antioxidant status values of all patients and control group members were measured. The patients (focal/generalized groups) and control group members were compared.RESULTS: This prospective study was completed with 58 eligible patients who met the inclusion criteria. There were 57 people in the control group. Total oxidant status (TOS) and OSI levels were higher in the seizure groups compared to the control group (p<0.05). The difference between the serum TOS and OSI levels of patients with generalized or focal onset seizures was statistically significant.CONCLUSION: Classifying patients according to their seizure types by looking at their oxidative stress levels can guide treatment (in terms of investigating antioxidant activity) and give an idea about prognosis. This study showed the importance of TOS and OSI levels in patients presenting with seizures. This was particularly evident in generalized onset seizures. An evaluation of serum TOS and OSI levels in patients presenting with seizures may help us in clinical diagnosis, treatment, and classification.Keywords: Epilepsy, total oxidant status, seizure types, total antioxidant status
Keywords: Tıp; Cerrahi Tıp Bilimleri; Acil Tıp; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Emergency Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; ACİL TIP; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; EMERGENCY MEDICINE; Acil Tıp Hizmetleri; Cerrahi; Emergency Medical Services; Surgery; Epilepsy; total oxidant status; seizure types; total antioxidant status; OXIDATIVE STRESS; ILAE COMMISSION; POSITION PAPER; CLASSIFICATION; DIAGNOSIS; MANAGEMENT; CAPACITY; MODEL; EEG